Peningkatan Kesejahteraan Perekonomian Driver Gojek Medan melalui Program Swadaya - Sutri Hulu; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Law of the Republic of Indonesia Number 13 of 1998 states that social welfare is a system of social life and livelihood, both material and spiritual, which is covered by a sense of safety, decency, inner and outer peace which makes it possible for every citizen to fulfill their physical, spiritual, and spiritual needs. and social matters that are as good as possible for oneself, family and society by upholding human rights and obligations in accordance with Pancasila. Segel and Bruzy (in Kusnadi, 2013: 8) say that social welfare is the prosperous condition of a society which includes health, economic conditions, happiness and quality of life of the people. To encourage welfare for drivers, Gojek Indonesia presents a program that is always held every year. Swadaya is one of the consistent programs presented by Gojek with the aim of reducing partners' operational costs, such as discount vouchers for vehicle maintenance, credit, and assistance with other daily needs, as well as access to financial services such as savings, loans, cheap insurance and partner children's scholarships. . Gojek Swadaya Program, which is an exclusive program to ease the operational burden on driver partners and their families. Launched in 2016, Gojek Swadaya has been used by more than 450 thousand driver partners per month and helps them save up to 15% of operational costs as a partner/driver. Apart from that, the Gojek self-help program helps drivers save more on their daily shopping needs.